التخصيص بالعرف وأثره في الفقه الإسلامي - مسعودي, خالد; صيد, خليل; مسعودي, سفيان (جامعة الوادي - University of Eloued, 2014)
In this study, we dealt with the allocation and its impact on Islamic jurisprudence. We mentioned the importance of the subject and its objectives and the method of this study. First, about the definition of the allocation and public and custom, and saying of scientist in custom, which allocates saying in The Quran and Sauna. Finally, we do some practicing about the allocation, where importance of this study, which is very appeared, we thank Allah and all praise to him, and his messenger peace be upon him.
ليسانس